KEARIFAN TRADISI AL-QUR’AN DALAM PROSES ENKULTURASI BUDAYA LOKAL - Ansori Ansori (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article shows the Qur’an’s wisdom on social transformation.The enculturation wisdom offered by The Qur’an is clearly showed on itsverses. Those wisdoms follow a certain pattern which started by first,admitting local traditions second, processing those local traditions by refusingsome of them in humanism consideration. Finally, a judgment istaken by refusing or accepting it with some modification. The missionoffered is intended to reach the moral goodness, create and protect thesocial order and it’s equilibrium.